Propuesta de una metodología de auditoría ambiental como herramienta para la prevención de desastres y minimización de riesgos ambientales en compañías envasadoras de gas licuado de petróleo (GLP). Caso Compañía Nacional de Gas CONGAS C.A. Planta de Envasado Salcedo - Azuero Patiño, Diego Fabián (2015)
This paper aims to present a proposal for environmental audit for marketing and packaging of Liquefied Petroleum Gas (LPG), in our case focused on Packaging Plant Salcedo National Gas Company CONGAS CA in the period January to December 2014. Nationally there are 10 companies engaged in the marketing and LPG bottling, between the main we have DURAGAS S.A. with 36.5%; AGIP GAS (ENI ECUADOR S.A) with 30.62% and CONGAS CA with 14.50% of market share in representing domestic LPG segment, all these comply with applicable environmental laws and regulations, therefore each company is subject to a review of environmental auditing. The Environmental Audit is a test that allows collecting information about possible errors or breaches of rules, laws or regulations on environmental protection, based marketing and LPG bottling to identify potential environmental impacts and take corrective actions required by the job audit performed. During the performance of this methodology the company is regulated by the Ministry of Environment which establishes standards and environmental laws contained in the Unified Text of Secondary Environmental Legislation (TULAS) by reference in its BOOK VI Unique Environmental Management System. The EIA is measured relative to a field based on the methodology of ISO 14000 and 19011 standards, obtaining evidence which helped to detect flaws in the packaging process.